2002
DOI: 10.1146/annurev.physiol.64.081501.160000
|View full text |Cite
|
Sign up to set email alerts
|

Renal Genetic Disorders Related to K+ and Mg2+

Abstract: The recent knowledge of the renal epithelial transport systems has exploded with the identification, cloning, and characterization of a large number of membrane transport proteins. The fundamental aspects of these transporters are beginning to emerge at the molecular level and are summarized in the accompanying contributions in this volume of the Annual Review of Physiology. The aim of my review is to integrate this body of knowledge with the understanding of the clinical disorders of human mineral homeostasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 185 publications
(207 reference statements)
1
19
0
Order By: Relevance
“…Affected patients present with normal or low blood pressure, hyperreninemia, metabolic alkalosis, and especially hypokalemia. [1][2][3] The disorder has been recently classified into three distinct phenotypes. [1][2][3] Antenatal Bartter syndrome, the most severe phenotype, is characterized by hydramnios, premature birth, life-threatening episodes of salt and water loss, and early onset of nephrocalcinosis.…”
Section: Background: the Management Of Inherited Hypokalemia Has Imprmentioning
confidence: 99%
See 2 more Smart Citations
“…Affected patients present with normal or low blood pressure, hyperreninemia, metabolic alkalosis, and especially hypokalemia. [1][2][3] The disorder has been recently classified into three distinct phenotypes. [1][2][3] Antenatal Bartter syndrome, the most severe phenotype, is characterized by hydramnios, premature birth, life-threatening episodes of salt and water loss, and early onset of nephrocalcinosis.…”
Section: Background: the Management Of Inherited Hypokalemia Has Imprmentioning
confidence: 99%
“…[1][2][3] The disorder has been recently classified into three distinct phenotypes. [1][2][3] Antenatal Bartter syndrome, the most severe phenotype, is characterized by hydramnios, premature birth, life-threatening episodes of salt and water loss, and early onset of nephrocalcinosis. Classic Bartter syndrome, which presents in infancy or early childhood, is characterized by marked salt wasting and hypokalemia leading to polyuria and polydipsia.…”
Section: Background: the Management Of Inherited Hypokalemia Has Imprmentioning
confidence: 99%
See 1 more Smart Citation
“…50 The hallmark of disorders that cause an increase in the activity of the ENaC is an increase in the urinary excretion of potassium. 51 Because blacks excrete less potassium in the urine than do whites, it is unlikely that sodium sensitivity in blacks is the result of an increase in the activity of the ENaC.…”
Section: Further Clues For Sodium Sensitivity In Blacks Based On Potamentioning
confidence: 99%
“…50 The hallmark of disorders that cause an increase in the activity of the ENaC is an increase in the urinary excretion of potassium. 51 Because blacks excrete less potassium in the urine than do whites, it is unlikely that sodium sensitivity in blacks is the result of an increase in the activity of the ENaC.A recent study by Pratt et al 38 showed that treatment with amiloride for 1 week caused a reduction in blood pressure in whites but a paradoxical increase in the blood pressure in blacks. Treatment with amiloride during this short time period reduced urinary potassium, with whites showing twice the reduction in potassium excretion as did blacks, although this ethnic difference was not statistically significant.…”
mentioning
confidence: 99%